Orthoglymma wangapeka gen.n., sp.n. (Coleoptera: Carabidae: Broscini): A newly discovered relict from the Buller Terrane, north-western South Island, New Zealand, corroborates a general pattern of Gondwanan endemism - Liebherr, James K. (2011)
Orthoglymma Liebherr, Marris, Emberson, Syrett & Roig-Juñent gen.n. (Coleoptera: Carabidae: Broscini) is described to accommodate the single type species Orthoglymma wangapeka Liebherr, Marris, Emberson, Syrett & Roig-Juñent sp.n., known from the Wangapeka Track, Kahurangi National Park, north-western South Island, New Zealand. Orthoglymma wangapekasp.n. is analysed cladistically along with a comprehensive array of 42 other broscine generic terminals and four out-group taxa, using information obtained from 73 morphological characters, and placed as adelphotaxon to the remainder of subtribe Nothobroscina, a clade distributed in New Zealand, southern South America and Australia. Based on fossil evidence for Carabidae, the occurrence of Orthoglymma wangapekasp.n. on the Buller Terrane, a geological feature once situated on the eastern margin of Gondwana, and early cladistic divergence of Orthoglymma from the remaining Nothobroscina, Orthoglymma wangapekasp.n. is interpreted as a Gondwanan relict. The New Zealand arthropod fauna is reviewed to identify other taxa in existence at the time of Cretaceous vicariance of New Zealand and Australia. These candidate Gondwanan taxa, all of which are specified using fossil data or molecular divergence-based estimates, are analysed biogeographically. Where phylogenetic hypotheses are available, primordial distributions are optimized using event-based, dispersal-vicariance (DIVA) analysis. The hypothesized Gondwanan-aged taxa demonstrate inordinate fidelity to the Gondwanan-aged geological terranes that constitute the western portions of New Zealand, especially in the South Island. Persistence of these relicts through a hypothesized 'Oligocene drowning' event is the most parsimonious explanation for the concentration of Gondwanan relicts in the Nelson, Buller and Fiordland districts of the South Island. Geographic patterns of Gondwanan-aged taxa are compared with distributions of taxa hypothesized to have colonized New Zealand across the Tasman Sea from Australia and New Caledonia, subsequent to Cretaceous vicariance. These post-Gondwanan taxa exhibit very different patterns of distribution and diversification in New Zealand, including: (i) abundant endemism in Northland, and the islands and peninsulas of the North Island; (ii) species geographically restricted to areas underlain by the youngest Rakaia and Pahau geological terranes; and (iii) species exhibiting exceedingly widespread geographic distributions spanning geological terranes of disparate ages. © 2011 The Authors. Systematic Entomology